Implementasi Jaringan RT/RW-Net Menggunakan Sistem Point-To Point Protocol Over Ethernet (PPPOE) Berbasis Mikrotik Routerboard Studi Kasus GayuhNet Semanan Jakarta Barat - Ambarita, Daniel; Yulianti (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2023)
The internet is a network that functions to connect electronic media to one another via computers, telephones, satellites and other communication systems. The RT/RW Net Network is an internet service provided to the community in a small area. The people of the Semanan area are currently having difficulties accessing the internet network because internet service providers are still quite expensive for some groups in the Semanan area. In this study, the authors collected data using the literature and questionnaire methods as material for consideration. The Net Semanan RT/RW network will be built using Mikrotik as network traffic as well as several network devices such as switches, HTB converters, indoor routers, POE (Power Over Ethernet), LAN cables, fiber optic cables, stations as connections to ISPs. LAN cable as a connection to the client and fiber optic cable to expand the network coverage area to the clients. With the RT/RW Net network in the Semanan area, the author hopes that the surrounding community can access the internet cheaply and more effectively and efficiently.